Nettle (Urtica dioica) Additive as a Growth Promoter and Immune Stimulator in Fish. (21st February 2023) - Zare, Mahyar; Esmaeili, Noah; Paolacci, Simona; Stejskal, Vlastimil
Abstract : Aquaculture will become an important food production sector for humans in the coming decades. However, disease outbreaks can be considered a significant obstacle to continually developing aquaculture. Plant powders and extracts are natural feed additives that, due to their bioactive compounds, including phenolic compounds, proteins, vitamins, and minerals, have antistress, antiviral, antibacterial, and antifungal effects on fish. One of these herbs is nettle ( Urtica dioica ), which has a long history of being used in traditional medicine. While it has been widely investigated in mammalian medicine, few studies have been done on aquaculture species. The positive effect of this herb on the growth performance, hematology, blood biochemistry, and immune system of fish species has been observed. When fish were exposed to pathogens, nettle-fed fish showed a higher survival rate and less stress than controls. Therefore, this literature review is aimed at reviewing the use of this herb in fish diets and its impacts on growth performance, hematology, blood biochemistry, liver enzymes, immune system stimulation, and challenges with pathogens.